What is in a tomato? Mapping the building blocks of food - Ahmed, Selena; Chien, Chi-Ming; Parra, John de la; German, Bruce; Jarvis, Andy; Lal, Vincent; Lartey, Anna; McDade, Marianne; Morgan, Katherine; Prenni, Jessica; Rajasekharan, Maya; Shafizadeh, Tracy; et al. (Frontiers Media, 2023)
When you bite into a tomato, what exactly are you eating? Join us for a tour of tomatoes, as we learn about the building blocks of food, known as biomolecules. Our tour explores the thousands of biomolecules in food, many of which play important roles in nutrition and health. An examination of tomatoes from various farms tells us that not all tomatoes have the same biomolecules. Lots of things affect the amounts and types of biomolecules in tomatoes, including their genetics, where and how they are grown, and even how they are stored and cooked. Our tour ends with a peek into a lab where scientists work on a global project to map all the biomolecules in foods. Welcome to an exciting frontier of science, where discoveries can lead to big improvements in the health of people and the planet.